Readiness of Philippine Coconut Authority in implementing the community and household level coconut processing in Brgy. Cabuloran, Dagami, Leyte. - Esber, Kate Eloise P.; Brazas-Lim, Ladylyn (Kate Eloise P. Esber, 2018)
This research study aimed to know the readiness of the Philippine Coconut Authority (PCA) in implementing the Community and Household Level Coconut Processing (CHLCP) in Barangay Cabuloran, Dagami, Leyte. Furthermore, this study identified the problems that were met by PCA while on the implementation process of the component. The research employed a mixed method design wherein the quantitative phase was used to scale the readiness of PCA while the qualitative phase was used to validate the data obtained from the first method. In scaling the readiness of PCA, the respondents were the KAANIB Coordinators from PCA. The informants who validated the data from the quantitative phase were the active farmers from Cabuloran. The research is grounded on Romero, Galeano, and Molina's readiness theory. This study used two of the theory's three pillars: people and process, which were helpful in explaining the data obtained from the study. Additionally, the implementation theory by Pressman and Wildavsky was used to evaluate the implementation process of PCA. The research findings show that the PCA was partially ready in implementing the program because some factors under the people pillar of the readiness theory were not met. However, the process pillar was effective while the PCA was carrying out the program. The partiality of their readiness can also be attributed to the ineffectiveness of the component at Cabuloran. The Super typhoon Yolanda became an intervening variable and became a glaring problem during the implementation process of the program.
A research paper (BASS Political Science) -- University of the Philippines, Tacloban.